“They are poor and violent”: Stereotypes and the Ibadan urban motor park space - Adeyemi Johnson Ademowo (University of Belgrade, 2016)
In this paper, we are interested in finding out how, and why, the interplay of poverty and violence – the park stereotypes – has problematised the motor park space, and consequently the culture that has evolved from that space. Of great concern to us are the origin and the operation of the park; the existence of these stereotypes, how, if ever, they relate and the implication of the interplay on the organization, operation and representation of the space vis-à-vis its relationship with the general public and government in Oyo State. Using Victor Turner’s concept of social drama, we hope to provide explanations for ruptured social relations on the park and answer why the public is so imbued with the stereotypes that they have refused to appreciate the internal mechanisms for resolving the ‘constant’ conflicts.